Molecular mobility in a thermoset as seen by TSR and DMA near Tg - Alves, N. M. (2001)
The conformational mobility of a polyester thermoset in the glass transition region is studied by dynamic mechanical analysis (DMA) and thermally stimulated recovery (TSR). All experiments were carried out in a commercial DMA apparatus, in the flexural mode. With this equipment thermally stimulated creep (TSCr) and thermal sampling (TS) experiments were also performed. Each TS curve was analysed according to a simple Voigt-Kelvin model where the retardation time follows the Arrhenius equation. Both the activation energy and the pre-exponential factor show the usual trends with temperature and present the well-known compensation phenomenon. The activation energy increases with temperature in the glassy state and even for lower temperatures the isolated processes are found to be highly cooperative. Two master curves for the storage modulus and the storage compliance were successfully constructed from the isothermal DMA experiments. The Vogel-Fulcher-Tamman-Hesse curve plot was directly obtained from the WLF parameters that were calculated without any non-linear fitting. The complementary character of the TSR and DMA techniques can be seen in an Arrhenius plot. The equivalent frequency of the TSR elementary processes increases with increasing temperature, with values around ~10-2.8 Hz. Some results obtained by simulation were shown, allowing to conclude that this increase of frequency is a consequence of the increase of the activation energy with temperature in a system showing a compensation behaviour.